Shimia sediminis sp. nov., a bacterium isolated from marine sediment in the East China Sea. Issue 4 (22nd April 2021) - Zhu, Suting; Chen, Can; Cheng, Yuping; Guo, Chaobo; Peng, Nan; Zhang, Weiyan; He, Shan
Abstract : A Gram-stain-negative, ovoid-shaped, motile and strictly aerobic bacterium, designated ZQ172 T, was isolated from marine sediment sampled on Zhoushan Island located in the East China Sea. Strain ZQ172 T grew optimally at temperatures of 25–30 °C, at NaCl concentration of 2.0 % (w/v) and at pH 7.0–8.5. Catalase and oxidase activities, urease, and nitrate reduction were positive. Indole production, methyl red reaction, H2 S production and hydrolysis of gelatin, starch, casein and Tweens 20, 40, 60 and 80 were negative. The major cellular fatty acid was summed feature 8 (C18 : 1 ω 7 c and/or C18 : 1 ω 6 c ). The only respiratory quinone was ubiquinone-10. The major polar lipids were phosphatidylethanolamine, phosphatidylglycerol, diphosphatidylglycerol and phosphatidylcholine. Comparative analysis of the 16S rRNA gene sequence showed highest similarities to Shimia aestuarii JC2049 T (97.5 %), Shimia abyssi JAMH 043 T (97.5 %) and Shimia thalassica CECT 7735 T (97.3 %). Phylogenetic analyses indicated that strain ZQ172 T clustered with the genus Shimia and was closely related to Shimia thalassica CECT 7735 T . The average nucleotide identity and digital DNA–DNA hybridization values between strain ZQ172 T and related species of the genus Shimia were well below the threshold limit for prokaryotic species delineation. The DNA G+C content was 59.6 mol%. Based on its phenotypic, chemotaxonomic and genotypic data, strain ZQ172 T is considered to be a representative of a novel species in the genus Shimia, for which the name Shimia sediminis sp. nov. is proposed. The type strain is ZQ172 T (=KCTC 62578 T =MCCC 1K03531 T ).